Digital research confidential : the secrets of studying behavior online - Hargittai, Eszter, 1973-; Sandvig, Christian (The MIT Press, 2016)
Behind-the-scenes stories of how Internet research projects actually get done.The realm of the digital offers both new methods of research and new objects of study. Because the digital environment for scholarship is constantly evolving, researchers must sometimes improvise, change their plans, and adapt. These details are often left out of research write-ups, leaving newcomers to the field frustrated when their approaches do not work as expected. Digital Research Confidential offers scholars a chance to learn from their fellow researchers' mistakes--and their successes. The book--a follow-up to Eszter Hargittai's widely read Research Confidential--presents behind-the-scenes, nuts-and-bolts stories of digital research projects, written by established and rising scholars. They discuss such challenges as archiving, Web crawling, crowdsourcing, and confidentiality. They do not shrink from specifics, describing such research hiccups as an ethnographic interview so emotionally draining that afterward the researcher retreated to a bathroom to cry, and the seemingly simple research question about Wikipedia that mushroomed into years of work on millions of data points. Digital Research Confidential will be an essential resource for scholars in every field.ContributorsMegan Sapnar Ankerson, danah boyd, Amy Bruckman, Casey Fiesler, Brooke Foucault Welles, Darren Gergle, Eric Gilbert, Eszter Hargittai, Brent Hecht, Aron Hsiao, Karrie Karahalios, Paul Leonardi, Kurt Luther, Virag Molnar, Christian Sandvig, Aaron Shaw, Michelle Shumate, Matthew Weber- Resumé vydavatel
Keywords: sociální sítě; internetové sociální sítě; sociální média; sociální výzkum; internet; social networks; Internet social networks; social media; social research; Internet; elektronické knihy; sborníky; electronic books; papers of several authors